Two new cicada species from Costa Rica (Hemiptera: Cicadomorpha: Cicadidae) with a key to the species of Fidicinoides in Costa Rica - Sanborn, Allen F.; Moore, Thomas E.; Young, Allen M. (Zootaxa, 2008)
The Neotropical cicadas Fidicinoides coffea Sanborn, Moore and Young and Fidicinoides guayabana Sanborn, Moore and Young are described as new species. This work validates the names previously assigned to these species which had been considered nomina nuda. Comparisons are made to other members of the genus found in Costa Rica. A summary of the biology of each new species is provided. The following new combinations, all for species formerly included in Fidicina, are proposed: Fidicinoides brisa (Walker 1850), F. cachla Distant 1899, F. flavibasalis Distant 1905, F. fumea Distant 1883, F. glauca Goding 1925, F. opalina (Germar 1821), F. passerculus (Walker 1850), F. sericans Stål 1854, F. spinicosta (Walker 1850), F. steindachneri Kuhlgatz & Melichar 1902, F. variegata Sanborn 2005, and F. viridifemur (Walker 1850). A key to the Costa Rican species of Fidicinoides is provided.